2005
DOI: 10.1007/s00425-005-1522-8
|View full text |Cite
|
Sign up to set email alerts
|

Localization of actin filaments on mitotic apparatus in tobacco BY-2 cells

Abstract: Actin filaments are among the major components of the cytoskeleton, and participate in various cellular dynamic processes. However, conflicting results had been obtained on the localization of actin filaments on the mitotic apparatus and their participation in the process of chromosome segregation. We demonstrated by using rhodamine-phalloidin staining, the localization of actin filaments on the mitotic spindles of tobacco BY-2 cells when the cells were treated with cytochalasin D. At prophase, several clear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Coordination of microtubules and microfilaments in the cortical cytoplasm plays a key role during directional expansion of cells as well as during positioning of the plane of cell division. Microtubules and microfilaments cooperate during cell division to coordinate the mitotic and cytokinetic apparatus (Panteris and Galatis, 2005;Yasuda et al, 2005;Collings, 2008; Petrá š ek and Schwarzerová , 2009). However, little information is available at the protein level to understand the mechanisms by which microtubules and microfilaments interact.…”
Section: Afh14 Serves As a Linker Protein Coordinating Microtubule Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordination of microtubules and microfilaments in the cortical cytoplasm plays a key role during directional expansion of cells as well as during positioning of the plane of cell division. Microtubules and microfilaments cooperate during cell division to coordinate the mitotic and cytokinetic apparatus (Panteris and Galatis, 2005;Yasuda et al, 2005;Collings, 2008; Petrá š ek and Schwarzerová , 2009). However, little information is available at the protein level to understand the mechanisms by which microtubules and microfilaments interact.…”
Section: Afh14 Serves As a Linker Protein Coordinating Microtubule Anmentioning
confidence: 99%
“…In support of this idea, in metaphase I and II, microfilaments codistribute with the spindle microtubules. During the second division, microfilaments intimately connect with the radiating microtubules and guide outgrowth of the phragmoplast (Schmit and Lambert, 1987;Traas et al, 1989;Staiger and Cande, 1991;Preuss et al, 2004;Yasuda et al, 2005). Drug-based experiments have shown that fragmentation of microfilaments leads to the disappearance of spindles and phragmoplasts.…”
Section: Afh14 Plays An Important Role In Cell Divisionmentioning
confidence: 99%
“…Actin/myosin involvement in mitosis has been deduced from studies that actin, myosin and titin are present in a variety of spindles [e.g., Table I of Forer et al, 2003;Robinson and Snyder, 2005;Yasuda et al, 2005;Fabian and Forer, 2007;Fabian et al, 2007b] and, also in a variety of cells, from studies of the effects of actin inhibitors, of myosin inhibitors or of genetic alterations to myosin [review in Table II of ; also Forer, 2005, 2007;Woolner et al, 2008]. In crane-fly spermatocytes in particular, the cells used for the experiments we describe herein, anaphase chromosome movement is altered by actin inhibitors cytochalasin D and latrunculin B, both of which cause depolymerization of actin filaments, and is altered by myosin inhibitors BDM and Y27632, both of which block myosin activity [Forer and Pickett-Heaps, 1998;Silverman-Gavrila and Forer, 2001;Fabian and Forer, 2005;Fabian et al, 2007a].…”
Section: Introductionmentioning
confidence: 99%
“…Three experiments were performed; in each, 1 of the biological replicas (independent transformants) included 5 experimental replicates. The constitutively expressed b-actin gene (ID: AB158612, Yasuda et al, 2005) was used for normalization.…”
Section: Accumulation Of Transcript Analysismentioning
confidence: 99%